Working with texts : a core introduction to language analysis - Carter, Ronald, 1947-; Beard, Adrian, 1951- (London ; New York : Routledge, 2008)
The core textbook in the popular Intertext series, Working with Texts introduces students to the main principles of language analysis, through real text examples. Featuring a wealth of contemporary examples of English in use, the book is supported by clear and accessible explication and commentary.
Includes bibliographical references (p. 255) and index.
Keywords: Linguistic analysis (Linguistics).